IMPLEMENTASI PROGRAM “CAKAP” DALAM MENGEMBANGKAN KARAKTER PEDULI LINGKUNGAN SISWA KELAS II SDN CISURU 01 CIPARI - Suyitno Suyitno; Wildan Nurul Fajar; Tugiono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the CAKAP Program (Cinta Alam melalui Karakter, Aksi, dan Pembiasaan / Love for Nature through Character, Action, and Habituation), the development of students' environmental care character, and the supporting and inhibiting factors in its implementation among second-grade students at SD Negeri Cisuru 01 Cipari. The study employed a qualitative approach with a case study design. The research participants consisted of 23 second-grade students and one classroom teacher. Data were collected through observation, interviews, and documentation. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the CAKAP Program was implemented through program socialization, the establishment of a clean classroom agreement, daily habituation activities through the CAKAP Ant Operation, the use of a mission tracking board, and student reflection activities. The implementation of the program demonstrated the development of environmental care character, as reflected in students’ increased awareness of maintaining cleanliness, growing sense of responsibility toward the classroom environment, enhanced social concern among peers, and the emergence of positive habits related to environmental cleanliness. Monitoring results showed that 18 out of 23 students were able to maintain environmental cleanliness independently, while 5 students still required periodic reminders. Supporting factors included students’ enthusiasm, the active role of teachers, the use of a mission tracking board, and school support. The challenges encountered involved differences in students’ levels of awareness, the ongoing process of habit formation, and time constraints during implementation. The CAKAP Program represents a habituation-based initiative that supports the development of environmental care character through direct experiences and active student participation in everyday school activities.